Obstetric Outcomes Associated with Fetal Cyanotic Congenital Heart Disease - Rossi, Robert M.; Divanovic, Allison; DeFranco, Emily A. (American Journal of Perinatology, 2019)
Objective To characterize obstetric outcomes associated with cyanotic congenital heart disease (CCHD) in a contemporary population.Study Design We conducted a population-based retrospective cohort study of all livebirths in Ohio (2006–2015). Obstetric characteristics of pregnancies complicated by fetal CCHD were compared with those without CCHD, excluding those with other anomalies and aneuploidy. The primary objective was to determine the risk of cesarean delivery among CCHD affected pregnancies. Multivariate logistic regression estimated the influence of CCHD on these obstetric outcomes.Results Among 1,463,506 live births in Ohio, there were 863 (0.06%) CCHD affected births. The overall cesarean rate was 45.9 versus 31.0% (p< 0.001) in CCHD compared with non-CCHD pregnancies. After adjusting for various confounders, CCHD affected pregnancies were associated with a higher risk for cesarean delivery (adjusted relative risk [aRR]: 2.0, 95% confidence interval [CI]: 1.6–2.4), preterm birth (PTB) (aRR: 1.5, 95% CI: 1.1–2.0), induction of labor (aRR: 1.2, 95% CI: 1.04–1.4), small for gestational age (SGA) birthweight (aRR: 2.4, 95% CI: 2.0–2.9), and fetal intolerance of labor (FIOL; aRR: 2.0, 95% CI: 1.6–2.4). Women with CCHD affected pregnancies were also less likely to undergo a trial of labor (aRR: 0.4, 95% CI: 0.3–0.5) prior to cesarean delivery.Conclusion Obstetric outcomes associated with CCHD include higher risk for cesarean delivery, PTB, SGA, and FIOL.
Keywords: congenital heart disease; cesarean; cyanotic; mode of delivery